Connection Leadership Head School, Teacher Discipline, and Teacher Responsibility for Teacher Performance - Lubis, Febrina Minda Eria; Neliwati, Neliwati (Universitas Muhammadiyah Enrekang, 2026)
The study aims to see the influence of Principal Leadership, Teacher Discipline, and Teacher Responsibility on teacher performance. The researcher used an ex post facto, quantitative approach. The study was conducted in June 2025 during the 2025 academic year. The population was all elementary school teachers in East Halangonan District, North Padang Lawas Regency, totaling 335 people from 31 elementary schools. The sampling technique used was proportional random sampling. The data collection technique used a questionnaire. The validity test used construct validity and content validity. Validity testing involved expert opinions (judgment experts). The reliability test used Cronbach's alpha. The instrument is considered reliable if its Cronbach's alpha is greater than 0.6. The data analysis used to test the hypothesis in this study was multiple regression analysis. The hypothesis criteria were accepted if the significance was less than 0.05. The results of the study indicate that: 1) there is an influence of principal leadership on the performance of public elementary school teachers, with a t-value of 2.063 with a significance level of 0.041; because the significance value is smaller than 0.05 (0.041<0.05), and the regression coefficient has a positive value of 0.126. 2) There is an influence of Discipline on the performance of public elementary school teachers with a t-value of 8.238 with a significance level of 0.000, because the significance value is smaller than 0.05 (0.000<0.05), and the regression coefficient has a positive value of 0.396. 3) There is an influence of Teacher Responsibility on teacher performance with a t-value of 4.034 with a significance level of 0.000, because the significance value is smaller than 0.05 (0.000<0.05), and the regression coefficient has a positive value of 0.188. 4) The test results obtained a calculated F value of 102.345 with a significance of 0.000. Because the significance value is smaller than 0.05 (0.000<0.05), the hypothesis that states